Tanshinone IIA reduces SW837 colorectal cancer cell viability via the promotion of mitochondrial fission by activating JNK-Mff signaling pathways - Jieensinue, Sayilaxi (BMC Cell Biol, 2018)
BACKGROUND: Mitochondrial homeostasis has been increasingly viewed as a potential target of cancer therapy, and mitochondrial fission is a novel regulator of mitochondrial function and apoptosis. The aim of our study was to determine the detailed role of mitochondrial fission in SW837 colorectal cancer cell viability, mobility and proliferation. In addition, the current study also investigated the therapeutic impact of Tanshinone IIA (Tan IIA), a type of anticancer adjuvant drug, on cancer mitochondrial homeostasis. RESULTS: The results of our data illustrated that Tan IIA promoted SW837 cell death, impaired cell migration and mediated cancer proliferation arrest in a dose-dependent manner. Functional investigation exhibited that Tan IIA treatment evoked mitochondrial injury, as witnessed by mitochondrial ROS overproduction, mitochondrial potential collapse, antioxidant factor downregulation, mitochondrial pro-apoptotic protein upregulation, and caspase-9-dependent apoptotic pathway activation. Furthermore, we confirmed that Tan IIA mediated mitochondrial damage by activating mitochondrial fission, and the inhibition of mitochondrial fission abrogated the proapoptotic effects of Tan IIA on SW837 cells. To this end, our results demonstrated that Tan IIA modulated mitochondrial fission via the JNK-Mff pathways. The blockade of the JNK-Mff axis inhibited Tan IIA-mediated mitochondrial fission and promoted the survival of SW837 cells. CONCLUSIONS: Altogether, our results identified mitochondrial fission as a new potential target to control cancer viability, mobility and proliferation. Furthermore, our findings demonstrate that Tan IIA is an effective drug to treat colorectal cancer by activating JNK-Mff-mitochondrial fission pathways. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12860-018-0174-z) contains supplementary material, which is available to authorized users.